Visual biofeedback balance training using wii fit after stroke: A randomized controlled trial - Barcala, Luciana; Collange Grecco, Luanda André; Colella, Fernanda; Garcia Lucareli, Paulo Roberto; Inoue SaLgado, Afonso Shiguemi [UNESP]; Oliveira, Claudia Santos (Society of Physical Therapy Science, 2013)
[Purpose] The aim of the present study was to investigate the effect of balance training with visual biofeedback on balance, body symmetry, and function among individuals with hemiplegia following a stroke. [Subjects and Methods] The present study was performed using a randomized controlled clinical trial with a blinded evaluator. The subjects were twenty adults with hemiplegia following a stroke. The experimental group performed balance training with visual biofeedback using Wii Fit® together with conventional physical therapy. The control group underwent conventional physical therapy alone. The intervention lasted five weeks, with two sessions per week. Body symmetry (baropodometry), static balance (stabilometry), functional balance (Berg Balance Scale), functional mobility (Timed Up and Go test), and independence in activities of daily living (Functional Independence Measure) were assessed before and after the intervention. [Results] No statistically significant differences were found between the experimental and control groups. In the intragroup analysis, both groups demonstrated a significant improvement in all variables studied. [Conclusion] The physical therapy program combined with balance training involving visual biofeedback (Wii Fit®) led to an improvement in body symmetry, balance, and function among stroke victims. However, the improvement was similar to that achieved with conventional physical therapy alone.
Keywords: Postural balance; Stroke; Visual biofeedback